1992
DOI: 10.2514/3.11475
|View full text |Cite
|
Sign up to set email alerts
|

Mixing and combustion studies using discrete orifice injection at hypervelocity flight conditions

Abstract: A Mach 13 operating point was achieved in the HYpersonic PULSE facility (HYPULSE) expansion tube and hydrogen injection studies were performed at this test condition. The experiments were conducted in a 2-x 1-in. combustor model employing three injector configurations: 1) a single, flush-wall, circular orifice; 2) two such orifices on opposite walls (the "dual" injector configuration); and 3) two orifices on the upper and lower walls (the "quad" injector configuration). The quad injectors were distinctly super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This will result in chemical kinetic limitations on the H 2 -air ignition and combustion processes. On the other hand, this limitation can partiallybe circumventedif an elevated concentration of oxygen is used in the test gas to increase the collision rates as suggested by Bakos et al 7 However, BenYakar 22 has shown that, in high-enthalpy ows, presented in this paper, ignition of hydrogen, injected transversely into a freestream of air, can be achievedin the near vicinity of the injector, even at low pL values. If ignition is achieved at low pressures, it is, therefore, likely that autoignition will occur at higher pressures because the Damköhler and Reynolds numbers increase linearly with pL in a realistic system.…”
Section: Experimental Approachmentioning
confidence: 91%
See 1 more Smart Citation
“…This will result in chemical kinetic limitations on the H 2 -air ignition and combustion processes. On the other hand, this limitation can partiallybe circumventedif an elevated concentration of oxygen is used in the test gas to increase the collision rates as suggested by Bakos et al 7 However, BenYakar 22 has shown that, in high-enthalpy ows, presented in this paper, ignition of hydrogen, injected transversely into a freestream of air, can be achievedin the near vicinity of the injector, even at low pL values. If ignition is achieved at low pressures, it is, therefore, likely that autoignition will occur at higher pressures because the Damköhler and Reynolds numbers increase linearly with pL in a realistic system.…”
Section: Experimental Approachmentioning
confidence: 91%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Because of the large stagnation enthalpies (greater than 3 MJ/kg) associated with high ight Mach numbers beyond Mach 8, currently only impulse facilities are capable of providing the required stagnation temperature and Mach number to replicate a combustor environment.…”
mentioning
confidence: 99%